Gold nanoparticles affect the antioxidant status in selected normal human cells - Daems, Noami; Penninckx, Sébastien; Nelissen, Inge; Van Hoecke, Karen; Cardinaels, Thomas; Baatout, Sarah; Michiels, Carine; Lucas, Stéphane; Aerts, An (International journal of nanomedicine, 2019)
This study evaluates the cytotoxicity of AuNPs coated with polyallylamine (AuNPs-PAA) and conjugated or not to the epidermal growth factor receptor (EGFR)-targeting antibody Cetuximab (AuNPs-PAA-Ctxb) in normal human kidney (HK-2), liver (THLE-2) and microvascular endothelial (TIME) cells, and compares it with two cancer cell lines that are EGFR-overexpressing (A431) or EGFR-negative (MDA-MB-453). Conjugation of Cetuximab to AuNPs-PAA increased the AuNPs-PAA-Ctxb interactions with cells, but reduced their cytotoxicity. TIME cells exhibited the strongest reduction in viability after exposure to AuNPs-PAA(±Ctxb), followed by THLE-2, MDA-MB-453, HK-2 and A431 cells. This cell type-dependent sensitivity was strongly correlated to the inhibition of thioredoxin reductase (TrxR) and glutathione reductase (GR), and to the depolarization of the mitochondrial membrane potential. Both are suggested to initiate apoptosis, which was indeed detected in a concentration- and time-dependent manner. The role of oxidative stress in AuNPs-PAA(±Ctxb)-induced cytotoxicity was demonstrated by co-incubation of the cells with N-acetyl L-cysteine (NAC), which significantly decreased apoptosis and mitochondrial membrane depolarization. This study helps to identify the cells and tissues that could be sensitive to AuNPs and deepens the understanding of the risks associated with the use of AuNPs in vivo.